The Breeding Population of the Rook, Corvus frugilegus (Aves, Corvidae) in Kharkiv, Ukraine: Nearly 22-times Decline in Numbers Over an 80-year Period - Brezghunova , O. O.; Sinna, O. I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Based on regular surveys of the distribution of rookeries and the number of nesting birds of Corvus frugilegus Linnaeus, 1758 carried out in 2002–2020 using the TRIM (TRends & Indices for Monitoring data), the trajectory of change in the rook population has been estimated. The total size of the breeding population of rooks in Kharkiv City has decreased by 95.4 % over the last 80 years, from 940 to 43 breeding pairs. The general trend for 1939–2020 is a moderate decline (multiplicative slope 0.980, standard error 0.004; p < 0.01). A similar trend was observed for 2002–2020 when surveys were regular, i. e. a moderate decline (multiplicative slope 0.920, standard error 0.021; p < 0.01). Rooks still use the centre of the city for nesting, as they did in the early 1940s, but from the 1980s they began to breed in the eastern part of Kharkiv, where most of the population is now concentrated. Rooks breed in two clustered colonies, one in the central and one in the eastern part of Kharkiv City, about 13 km apart. The colonies are not numerous (all less than 50 pairs) in the last 10 years. The possible causes of the decline of the rook population in Kharkiv City are discussed.